Effect of early water contact on solubility of glass ionomer luting cements - (:unkn) unknown (My University, 1998)
STATEMENT OF PROBLEM: Glass ionomer cements are susceptible to attack by moisture during the initial setting period that can result in an increased solubility. PURPOSE: This study was to evaluate the solubility of glass ionomer luting cements immersed in distilled water at early stages after mixing. MATERIAL AND METHODS: Four commercial glass ionomer cements were used (Ketac-Cem, Fuji Ionomer I; AquaCem; AquaMeron). For each material, 5 resin cement holders were made with 2 circular cavities (diameter = 5 mm; depth = 2 mm). One minute after start of mixing, the specimens were placed in a humidifier at 37 degrees C and 100% relative humidity. After 2, 5, and 8 minutes storage time, they were immersed in 50 mL of distilled water in a glass weighing bottle where they were stored for 3 hours at 37 degrees C. Next, the specimens were removed and the water was evaporated from the weighing bottle at 130 degrees C for 2 hours. The difference between the final and initial weights of the bottle was taken as amount of solubility. Data were analyzed by analysis of variance and Duncan's test. RESULTS: Solubility was greatest at 3 minutes immersion time and least at 9 minutes. The lowest cement loss was for AquaCem at 9 minutes immersion time (1.68 mg/cm2). The greatest loss was for Fuji Ionomer I after 3 minutes immersion time (14.98 mg/cm2). Solubility of cements decreased by 39% for Ketac-Cem, 61% for Fuji Ionomer I, 38% for AquaCem, and 37% for AquaMeron when the specimens were immersed in water 6 minutes after mixing. Comparison of all 4 cements revealed a relatively large difference between loss of substance from AquaCem and AquaMeron, and the 2 other conventional glass ionomer cements, Keta-cCem and Fuji Ionomer I. CONCLUSIONS: Increasing the time from start of mixing until immersion in water from 3 to 9 minutes resulted in a marked decrease in loss of substance from the surface of all 4 cements. Water-hardening glass ionomer cements (AquaCem and AquaMeron) were less sensitive to early water contamination.
Keywords: Materials Testing; Time Factors; Surface Properties; Water; Acrylic Resins; Chemical Phenomena; Chemistry, Physical; Desiccation; Glass Ionomer Cements; Humidity; Immersion; Magnesium Oxide; Polycarboxylate Cement; Solubility; Zinc Oxide